Emerging business models for the cultural commons. Empirical evidence from creative cultural firms. Issue 3 (3rd July 2021) - Dameri, Renata Paola; Moggi, Sara
ABSTRACT: Cultural assets can be seen as a particular type of commons as they belong to a group or society that inherits them from past generations, maintains them in the present and preserves them for the benefit of future generations. The cultural commons are exposed to specific forms of the tragedy; however, little is known about how the tragedy of cultural commons can be managed and overcome. This study argues that cultural and creative firms could play a pivotal role in addressing this issue, and it inductively develops a business model for Cultural and Creative Firms to manage cultural assets as commons that are threatened with neglect or misuse. In doing this, a multiple-case study is employed to develop a new business model. This study contributes to knowledge about how creative and cultural firms can implement cooperative and participative business models to address the fragility of cultural commons.